POTENSI KESWADAYAAN MASYARAKAT DALAM IMPLEMENTASI PROGRAM PENINGKATAN KUALITAS PERMUKIMAN (PKP) (Studi Kasus: Kelurahan Pringapus, Kecamatan Pringapus Kabupaten Semarang) - Dewi, Widyaningtyas Kartika (Jurnal Pengembangan Kota, 2014)
The house is one of the basic human needs and have significance in the development of social life, economy and identity of its inhabitants. Limitations of the funds or budgets from the government in addressing the housing needs of the community led to the current government can reach out to new formal sector only. It is displaced lack access to Low-Income Communities to get home. Of self-governing society to build a house with many limitations in terms of manpower, materials and costs, so that the housing conditions of low-income communities become unfit for occupancy. For that government to the approach followed by Kemenpera Housing Improvement Program. Sub-standart housing upgrading program is intended as a stimulant or stimulus to the community in order to develop themselves and want to contribute to the development. The purpose of this study to measure and assess the extent of potential self- supporting community in the implementation of sub-standart housing upgrading program is applied in the Village Pringapus. This study uses the method mix method, mixing method used sequential explanatory design using patterns. Collection and analysis of quantitative data is beginning, after the completion followed by qualitative data collection and analysis, and interpretation of the analysis performed. Indicators and variables to be tested or analyzed are forms of non-governmental organizations and the amount of public good issued in the form of money, labor or material that is processed by techniques of quantitative analysis used descriptive statistics and explanations. While the sources of non-governmental organizations to build houses as well as the pattern of development palaksanaan processed using qualitative descriptive analysis, how to capture this data focuses on the nature exploratory interviews and field observations. The results of this study, the average total pure self-help communities make improvements issued a total of Rp 10,224,985 unloading, so self-released the 2-fold greater than with stimulants provided only Rp 5,000,000. As for the people who repair some of the average self-RP issued 2.7266 million, although this value is not too big but when viewed from the type of repair that is lightweight and does not require a large fee, a nominal 2 jt rupiah is relatively high when compared with funds stimulants. This shows that the potential for community-owned self-help program beneficiaries in the Village Pringapus PFM is very high. Apart from the magnitude-governmental organizations, community-owned self-help potential is also evident from the pattern of building a house. Society has a variety of ways as the efforts made to build his house, as done by yourself, using a carpenter, and mutual cooperation. The third way has a different essence, but in ways that use these beneficiaries is high potential in an effort to build a house. The high potential of the community indicate that the approach taken by the government through Housing Improvement program (PKP) is successful. It is evident that the approach taken by the government is able to encourage the willingness and the willingness of society to berswadaya in the implementation of their housing. But all this success can not be separated by BKM Sedya Mulya role that has empowered leading independent predicate.Â